Implementing the Circular Economy for Sustainable Development, by Hans Wiesmeth, Amsterdam, Netherlands: Elsevier, 2020. 318 pp., 105. ISBN: 9780128217986 - Rahmatika, Maula Fadhilata (Economics Departement, Faculty of Business and Economics, Universitas Surabaya, 2025)
Book Review: Implementing the Circular Economy for Sustainable Development, by Hans Wiesmeth, Amsterdam, Netherlands: Elsevier, 2020. 318 pp., 105. ISBN: 9780128217986